PENGARUH TEMPERATUR TERHADAP NILAI KAPASITANSI ELEKTRODA SUPERKAPASITOR GRAPHENE BERBASIS BAMBU BETUNG (Dendrocalamus asper) - Amaliah, Fia; Sahara, Sahara; Fuadi, Nurul (JFT : Jurnal Fisika dan Terapannya, 2018)
This study aims to analyze the effect of temperature variations on the capacitance of graphene material supercapacitor electrodes from bamboo material Betung (Dendrocalamus asper). The results obtained are graphene reduction can be synthesized by the hummer method which is reduced using Zn and continued with a thermal process with different temperature variations. The data obtained shows that from the GO, rGO 80 ° C, and 200 ° C rGO samples the largest capacitance value is the 200 ° C rGO sample, which is 8.87 × 10-3 F / gram with d-spacing 3.821082 Å, while the capacitance value for GO and rGO 80 ° C samples respectively 2.23 × 10-5 F / gram with d-spacing 3.668773 Å and 1.67 × 10-4 F / gram with d-spacing 3.680739 Å. This happens because the thermal effect is given, the greater the temperature given, the more pores are formed and the surface area will also be larger which results in more ion absorption and electron transfer on the electrode surface. However, if the given temperature is too large then the pore structure will be damaged and produce a low surface area. All samples that have the largest capacitance at the smallest pay rate are 10 mV / s.